Spirituality in Modern Education as an Ideological Concept - Karpova, N. K.; Mareev, V. I.; Petrova, N. P.; Uvarovsky, A. P. (Current Research in Language, Literature and Education Vol. 2, 2021)
The study examines the phenomenon of "spirituality" as an ideological concept in modern education, identifying its underlying senses as ideologemes.The performance of a person's activity and its evaluation in terms of paramount values are regarded as acceptance criteria for ideologemes. The authors see the methodological aspect of personal spiritual revelation as one of the fundamental directions in pedagogy, shifting the focus of studies to hermeneutic principles in studying spiritual experience. The central goal of pedagogical activity is to reveal an individual's deep inner world through the use of a hermeneutic approach.